Analysis of single nucleic acid molecules with protein nanopores. - Maglia, G; Heron, A; Stoddart, D; Japrung, D; Bayley, H (2010)
We describe the methods used in our laboratory for the analysis of single nucleic acid molecules with protein nanopores. The technical section is preceded by a review of the variety of experiments that can be done with protein nanopores. The end goal of much of this work is single-molecule DNA sequencing, although sequencing is not discussed explicitly here. The technical section covers the equipment required for nucleic acid analysis, the preparation and storage of the necessary materials, and aspects of signal processing and data analysis.